Особливості стоматологічного статусу дітей з різними рівнями психічного здоров’я - Дац, Валерія Валеріївна; Dats, V. V. (My University, 2020)
Показники стоматологічного статусу дітей корелюють з численними біологічними, фізіологічними та соціальними чинниками – від проживання в певному регіоні, що характеризується особливостями мінерального складу питної води, переважаючим модусом харчування населення та специфікою впливу локального біогеоценозу й поточної техногенної ситуації, до рівня загальної освіченості їхніх батьків, доступності стоматологічної допомоги для населення, проведення заходів профілактичного спрямування зі збереженням стоматологічного здоров’я. Стан психологічного благополуччя, а тим більше стан психічного здоров’я дитини має значний вплив на дотримання нею рекомендацій про забезпечення оптимального стану здоров’я ротової порожнини. Вивчення впливу стану психічного здоров’я дітей на стан здоров’я їх ротової порожнини є необхідним для подальшого формування висококонгруентних і персоніфікованих рекомендацій про догляд за зубами в кожній із груп дітей з різними рівнями психічного здоров’я (РРПЗ). Мета дослідження: визначити особливості показників стоматологічного статусу дітей з РРПЗ. Контингенти та методи. На базі КУ «Обласна клінічна стоматологічна лікарня» ЗОР за умов інформованої згоди батьків з дотриманням принципів біоетики було обстежено 100 дітей з різноманітними стоматологічними захворюваннями, які відрізнялись рівнем психічного здоров’я та демонстрували реакції одонтофобічного характеру. Їх було розділено на такі чотири групи: першу групу (Г1) склали 30 хворих на аутизм, другу групу (Г2) – 30 хворих на олігофренію легкого ступеня, третю групу (Г3) – 20 хворих на синдром дефіциту уваги та гіперактивності (СДУГ), четверту групу (Г4) – психічно здорові діти. Визначення стоматологічного статусу було проведено за допомогою розрахунку індексу кп+КПВ, РМА та Green-Vermillion. Indicators of dental status in children correlate with numerous biological, physiological and social factors, from living in some region characterized by the specifics of the mineral composition of water, the prevailing mode of nutrition in the population and the specifics of the impact of local biogeocoenosis and current technological situation, to the level of general education of their parents, the availability of dental care for the population, the implementation of preventive measures for the preservation of dental health. The state of psychological well-being, and moreover, the state of mental health of the child has a significant impact on compliance with recommendations to ensure the optimal health of the oral cavity. The study of the effect of children's mental health on the health of their oral cavity is necessary for the further formation of highly congruent and personified recommendations for the care of teeth in each group of children with different levels of mental health (DLMH). Purpose of the study. The purpose of the study: to determine the characteristics of indicators of dental status of children with DLMH. Contingents and methods. On the basis of Regional Clinical Dental Hospital, under the conditions of informed consent of parents and according principles of bioethics, 100 children with a variety of dental diseases with different levels of mental health, with odontophobic reactions were examined. They were divided into the following four groups: the first group (G1) consisted 30 patients with autism, the second group (G2) consisted 30 patients with oligophrenia of the mild degree, the third group (G3) consisted 20 patients with ADHD, the fourth group (G4) consisted mentally healthy children. Determination of dental status was carried out by calculating the index of caries, PMA index, Green-Vermillion hygienic index. Results. The features of stomatological status in children with different levels of mental health are revealed based on established dental indexes analysis. In G1, in comparison with the rest of the groups, the caries intensity and the number of patients with strongly pronounced caries intensity were significantly higher. Taking into account the notable difference between the indicators of caries intensity in children with autism and children without autistic manifestations, one can state that one of the leading etiological factors of this pathology is the presence of bruxism, which is the most characteristic for children with autism that leads to a significant damage to the enamel. In the G1 and G2 compare the G3 and G4, the prevalence of poor oral hygiene was significantly higher. In children with G2, high indicators of the Green-Vermillion index are due to frequent entry into the mouth of foreign objects that are microbiologically contaminated, and frequent use of food with hands without preliminary washing. In G1, instead, poor oral hygiene level is determined by the high intensity of their carious process and the neglect of the rules of adequate oral sanitation. In G3 compare the rest of groups, the gingivitis intensity and the number of patients with strongly pronounced intensity of gingivitis predominantly prevailed. Such a high level of intensity of the inflammation process in the gum in children of this group is due to frequent gum injury during the activity of the game and too intense brushing of teeth in an attempt to reduce the time of this hygienic procedure.
Odontophobic reactions in children with different level of mental health: pecularities of stomatologic status in children with different level of mental health
Keywords: стоматологічний статус; індекс кп+КПВ; індекс РМА; гігієнічний індекс Green-Vermillion; dental status; PMA index; Green-Vermillion hygienic index